THE ROLES OF TEMPE HOUSEHOLD INDUSTRY ON OVERCOMING POVERTY IN PONCOSARI VILLAGE, SRANDAKAN SUB DISTRICT, BANTUL DISTRICT - Kemal Wirawan Wicaksono; Ken Suratiyah; Lestari Rahayu Waluyati (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2013)
This study aims to determine (1) the costs, revenues, and profits by domestic tempe industry (2) employment by domestic tempe industry (3) feasibility and consiraints faced by domestic tempe industry (4) the role of domestic tempe industry in overcoming poverty. The basic method of this study is analytical descriptive study, the stipulation of respondent was determined by census and interviewed all households still produce tempe. Data analysis through R/C, π/C, employees productivity, total Break Event Point, indicators of well-being (GSR) and indicators of poverty (Sayogyo, BPS, and World Bank). The result showed that : (1) the average total cost of Rp 139.966.917,00/year, household income Rp Rp 24.812.733,00/year, a profit of Rp 6.366.733,00/year (2) R/C of 1,17; π/Cn0f 4,5%; employees productivity of Rp 110.572/HKO; totality Break Event Point of Rp 11.262.175 (3) the tempe industry is feasible to be developed (4) the contribution of domestic tempe industry revenue is 94,72% (5) the role of domestic tempe industry to absorb labor in the family and outside the family, increase household income and reduce the number of poor households.